Environmental pH and peptide signaling control virulence of Streptococcus pyogenes via a quorum-sensing pathway - Hackwon Do (Nature Portfolio, 2019)
The mechanism by which environmental pH controls the virulence of the pathogen Streptococcus pyogenes is unclear. Here, Do et al. show that changes in pH affect the activity of the virulence regulator RopB via its interaction with a quorum-sensing peptide signal.